KAJIAN UNDERGROUND ECONOMY DAN KAITANNYA DENGAN PENERIMAAN PAJAK DI INDONESIA - Fakhri Hafidzul Azhar; Gama Putra Danu Sohibien (Seminar Nasional Official Statistics, 2020)
Underground economy is income generated from economic activities, both legal and illegal, which are not included in the calculation of Gross Domestic Product (GDP). Underground economy activities that are allowed to continue to develop will result in loss of tax revenue. To overcome this, a tax amnesty policy was implemented, with the aim of minimizing the lost tax revenue, but it is not yet known whether this goal can be achieved or not. This study aims to provide an overview of the variables used, measure the size of the underground economy and the lost tax revenue due to the underground economy, and compare the average lost tax revenue before and after the tax amnesty. The measurement of underground economy and lost tax revenue is carried out through a monetary approach using the Error Correction Model method and the comparison of the average lost tax revenue using the average difference test. The results showed that there was an increasing trend in the variable money supply, ADHK GDP, BI interest rates and exchange rates and a downward trend in the variable ratio / tax burden, inflation and world oil prices. The size of the underground economy in Indonesia from 2005 to 2018 on average reached 34.157 trillion rupiah or 1.84% of GDP. The average lost tax revenue reached IDR 4 trillion or 0.22% of GDP. The tax amnesty that has been implemented in Indonesia since 2015-2018 has not been able to achieve the desired goals.underground economy, tax amnesty, error correction model (ECM), uji beda rata-rata dua populasi